Pengaruh Citra Merek, Kualitas Produk dan Harga Terhadap Keputusan Pembelian melalui Kepercayaan Konsumen pada Produk Stuck Original - Pratama, Dian Wahyu; Santoso, Suryono Budi (Diponegoro Journal of Management, 2018)
Based on the interview with 5 people who know Stuck Original there are some problems that affect the decline in sales. logos, models, materials, and prices are some of the things that affect the sales decline. So this research use independent variabel of brand image, product quality, and price. Intervening variabel is consumer trust and dependent variabel is purchasing decision.This study aims to analyze how the influence of brand image, product quality, and price to purchase decisions through consumer trust in the Stuck Original products.Sampling method used in this research is non-probability with purposive sampling technique The samples collected were 150 respondents who had bought the original stuck product at least once. The method of analysis used is SEM includes test of normality, outliers, reliability test, and goodness of fit.The results showed that the brand image, product quality, price, and consumer confidence significant to the purchase decision. consumer trust has the most significant affect on purchasing decisions with a loading factor of 0.79. brand image and product quality has the same loading factor value in affect consumer trust is 0.35. and last price has loading factor value in affect consumer trust is 0,31.